Antioxidant, aroma, and sensory characteristics of Maillard reaction products from Urechis unicinctus hydrolysates: development of food flavorings - Du, Mengdi; Yu, Wei; Ding, Ning; Jian, Mengqi; Cheng, Yongqiang; Gan, Jing (Frontiers in Nutrition, 2024)
To develop food flavorings with a delicious taste and an anti-oxidation effect, in this study, the glucose Maillard reaction was used for hydrolysates of Urechis unicinctus. The various biological activities of Maillard reaction products (MRPs) and their antioxidant capacity were evaluated. The results showed that the unique fishy odor substances of seafood in MRPs were reduced, indicating that the Maillard reaction improved the flavor of the hydrolysate of Urechis unicinctus. Meanwhile, MRPs exhibited more competitive radical scavenging activities compared to the hydrolysate. Moreover, MRPs demonstrated a considerable potential to protect against 2,2'-Azobis (2-methylpropionamidine) dihydrochloride (AAPH)-induced oxidative stress in a cell model in vitro and in a zebrafish model in vivo. Finally, a novel food flavoring was produced with MRPs as raw material, while the sensory qualities were deemed acceptable. In consequence, during industrial production, MRPs of Urechis unicinctus hydrolysate act as a high-quality raw material for functional flavorings and provide an effective way for the utilization of marine resources.Flavorings are usually food ingredients that are used to be added in small quantities to other foods to improve their flavor (deodorize, enhance freshness, relieve grease, etc.)(1).The flavoring industry has a wide range of products and a large sales volume, especially in China and other south-central Asian countries. The flavoring industry is developing rapidly, and the annual production of flavoring can be more than ten million tons. Especially in recent years, with the rapid development of society, people's living standards are improving at lightning speed, and the majority of consumers on the requirements for seasonings are also on the rise. Compared with the popular flavorings sold in the market now, people's requirements for flavorings are not only reflected in the color and flavor but also in being natural and environmentally friendly, green and safe, with specific nutritional properties.